Pengaruh supervisi akademik kepala sekolah, iklim kerja sekolah dan disiplin kerja terhadap kepuasan kerja guru SLB se Kota Yogyakarta tahun ajaran 2013/2014 - Wisnu Satria Ghautama (Universitas Sarjanawiyata Tamansiswa, 2015)
The research aims to understand: (1) The combined influence of Principal academical supervision, school working atmosphere, and working discipline on Yogyakarta city Special School Teachers working satisfactory, (2) The influence of principal academical supervision to Yogyakarta city Special School teachers working satisfactory, (3) The influence of school working atmosphere on Yogyakarta city Special School teachers working satisfactory, and (4) The influence of working discipline on Yogyakarta city Special School teachers working satisfactorily. The population in this research is all Yogyakarta City’s Special School Teacher, counted as 208 teachers. The research sampling method was using proportional random sampling using 137 teachers selected by Harry King monogram with a level of significance at 5%. The data was gathered using survey tested on 30 teachers qualified in terms of validity via Pearson Correlation technique and reliable based on alpha Cronbach value. The data were analyzed by means of double regression and partial correlation after it was tested in the prequalification analysis by means of multicollinearity, normality and also linearity test. The research analysis shows the principal academical supervision and working satisfaction was categorized on a higher level as well as school working atmosphere whereas working discipline was on a high level only. The double regression analysis revealed: (1) There is a positive and significant influence from principal academical supervision, school working atmosphere, and working discipline combined together on Yogyakarta City’s Special School teachers working satisfactorily. It means that the better principal academical supervision, school working atmosphere, and working discipline generate better teachers working satisfactorily. The partial correlation analysis revealed (2) There is a positive and significant influence from principal academical supervision on Yogyakarta City’s Special School teachers working satisfactory, meaning that the better principal academical supervision create better school teacher working satisfactory, (3) There is a positive and significant influence from school working atmosphere on Yogyakarta City’s Special School teachers working satisfactory meaning that the better school working atmosphere create better school teacher working satisfactory, and (4) There is no a positive and significant influence, partially, on working discipline level with school teachers working satisfactorily. It means that either high or low, working discipline doesn’t give significant effect on teachers working satisfactorily.